Some Human Management Aspects of M&A in Japan—Obstacles and Opportunities Offered to Foreign Companies (Malaysian Management Journal, 1997)
Out-in mergers and acquisitions activities in Japan have gradually increased but stay at a level extremely low compared with the situation in the Western World. Regulatory aspects remain important to explain this, but despite rapid changes in the socio-cultural environment, some idiosyncracies resulting from the concept of company remain. Japan is undertaking rapid soda-cultural changes and we should avoid being dragged into past perceptions far away from the modern reality. Nevertheless, as these characteristics lead, even today in a period of transition, to different management rules and labour attitudes and behaviour, they should still be considered with great care when doing business in Japan.